Synthesis of optimal stabilization of helicopter time and frequency methods - Кривоносенко, О.П.; Білак, Н.В.; Тимошенко, Н.А. (Proceedings of National Aviation University, 2008)
The research of helicopter stabilization system, as unstable plant, which are directed to confirmation of possibility to carry out synthesis of optimal structures of stabilization system with the help of frequency and time methods, are fulfilled in this article.